SEISMIC BROADBAND OCEAN-BOTTOM DATA AND NOISE OBSERVED WITH FREE-FALL STATIONS: EXPERIENCES FROM LONG-TERM DEPLOYMENTS IN THE NORTH ATLANTIC AND THE TYRRHENIAN SEA - Dahm T.; Tilmann F.; Morgan J.P. (My University, 2006)
In a comparative study of two long-term deployments we characterize the seismic noise on the seafloor in the North Atlantic south of Iceland and in the Tyrrhenian Sea north of Sicily. We estimate the teleseismic body-wave detection threshold to be approximately magnitude 6.0 at frequencies below the microseismic band (f < 0.1 Hz) on vertical components at the quietest sites in both regions. At the microseismic peak (~ 0.25 Hz) in the North Atlantic, the minimum magnitudes for events to be recorded most of the time are Mw 7.0 for the Tyrrhenian Sea deployment and above 8 for the North Atlantic deployment. By correlating seismic noise and oceanic waveheight amplitudes we are able to find the major generation areas of microseismic noise in the North Atlantic. Although the high noise of secondary microseisms at 0.24 Hz is generated far away from the ocean-bottom stations at three near-coastal regions, the microseismic noise at about 1 Hz is generated directly at the stations. We present a technique to estimate the noise generation areas prior to future deployment by using noise at nearby land stations. The ambient low-frequency noise below 0.1 Hz occurs mainly on horizontal components and is probably induced by seafloor-current-induced tilt. The power spectral density of this noise varies by a factor of up to 10,000 between different stations and deployment sites, indicating in some cases wobbling deployments, possible problems of frame weakness, and a possible higher noise sensitivity of external packs to seafloor currents. Cross-coupling between horizontal and vertical channel noise is strong at some of our stations, demonstrating that the leveling mechanics can be further improved to reduce vertical channel noise.